TINGKAT PENGETAHUAN PASIEN PROGRAM PENGELOLAAN PENYAKIT KRONIS DIABETES MELITUS TENTANG TUBERKULOSIS PARU DI UPT PUSKESMAS TELADAN MEDAN - NAUFAL AL FARISI SIREGAR (LP2MTBM MAKARIOZ, 2021)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion,insulin action, or both The latest estimates show a global prevalence of 422 million people with diabetes in 2014. Indonesia isranked one of the world's top five worst affected nations for people living with diabetes. Program pengelolaan penyakit kronis(PROLANIS) aims at participants with chronic disease type 2 diabetes mellitus to achieve a healthier life and maintainoptimal quality of life. Tuberculosis is a disease that can be at greater risk for people who suffer type 2 diabetes mellitus.To determine the knwoledge level of PROLANIS patients with type 2 diabetes mellitus about pulmonary tuberculosis.This study is descriptive research and the sampling technique used was total sampling with a population of all PROLANISpatients with type 2 diabetes mellitus at UPT Puskesmas Teladan Medan. Data collection techniques use the questionnairesthat distributed to PROLANIS patients with type 2 diabetes mellitus. Based on research results reporting on 43 respondents,29 respondents (67,64%) have good knowledge level about pulmonary TB disease, 13 respondents (30,23%) have enoughknowledge level and 1 respondent (2,33%) have less knowledge level.